Using Posterior EEG Theta Band to Assess the Effects of Architectural Designs on Landmark Recognition in an Urban Setting - Rounds, James D.; Cruz-Garza, Jesus Gabriel; Kalantari, Saleh (Frontiers in Human Neuroscience, 2020)
The process of urban landmark-based navigation has proven to be difficult to study in a rigorous fashion, primarily due to confounding variables and the problem of obtaining reliable data in real-world contexts. The development of high-resolution, immersive virtual reality technologies has opened exciting new possibilities for gathering data on human wayfinding that could not otherwise be readily obtained. We developed a research platform using a virtual environment and electroencephalography (EEG) to gather preliminary evidence about the neural processes associated with landmark usage and recognition during urban navigation tasks. By adjusting the architectural parameters of different buildings in this virtual environment, we isolated and tested specific design features to determine whether or not they served as a target for landmarking. EEG theta band (4-7 Hz) event-related synchronization (ERS) over posterior scalp areas was evaluated on twenty-one participants at the time when they observed each target building along a predetermined self-paced route. A multi-level linear model was used to investigate the effects of salient architectural features on posterior scalp theta ERS. Our results support the interpretation that highly salient architectural features—those that contrast sharply with the surrounding environment—are more likely to attract visual attention, remain in short-term memory, and potentially activate brain regions associated with wayfinding compared with non-salient buildings. After establishing this main aggregate effect, we tested hypotheses about specific salient architectural features. The buildings that most strongly associated extended gaze time, location recall accuracy, and changes in posterior theta-band ERS with landmarking in our study were those that incorporated rotational twist designs and natural elements such as trees and gardens. Other building features, such as unusual façade patterns or building heights, were to a lesser extent also associated with landmarking.